Analisis Kesenjangan Pengembangan Kompetensi Pedagogik Guru PGMI: Kajian Kritis Berbasis Teori Konstruktivistik - Anita Puspa Meilina (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The urgency to strengthen the pedagogical competence of Islamic Elementary Teacher Education (PGMI) teachers has increased in line with 21st-century learning demands, which emphasize critical thinking, collaboration, and meaningful learning. However, in practice, many PGMI teachers still face significant gaps in understanding and applying constructivist approaches effectively. This article aims to analyze these gaps and evaluate the potential for developing pedagogical competencies within the framework of constructivist theory. This study adopts a qualitative approach using library research methods, gathering secondary data from scholarly literature, educational policies, and previous relevant studies. Data analysis was conducted through content analysis, applying the Miles and Huberman model. The findings reveal a persistent reliance on conventional teaching methods, limited pedagogical literacy regarding constructivism, and insufficient integration of theory into teacher education curricula and training. The study concludes that systemic reforms are required in curriculum design, teacher training, and institutional partnerships to bridge these pedagogical gaps. This article contributes both conceptually and practically to the development of constructivist-based learning models in Islamic elementary education. Field-based follow-up research is recommended to empirically strengthen these findings.